2004
DOI: 10.4049/jimmunol.173.5.3261
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Recombination and Chain Pair Biases Greatly Influence the Primary γδ TCR Repertoire in the Thymus of Adult Mice

Abstract: Analyses of the rearrangement status of the TCRγ and TCRδ chain loci in progenies of individual γδ thymocytes showed a hierarchy of the different Vγ and Vδ gene segments to participate in a recombination reaction. Moreover, individual TCRγ chains only pair efficiently with a variable number of TCRδ chains. Interestingly, these two parameters are inversely correlated such that the TCRγ and TCRδ chains that rearrange more often show a higher level of restriction in their pairing capabilities. Our data suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…An attendant prediction of this model is that all i-IELs with Tcrg gene rearrangements involving the C γ 1 cluster on both chromosomes exclusively exhibit V γ 5 gene rearrangements. However, analysis of Tcrg gene rearrangement pattern in V γ 5 + γδ thymocyte clones does not support this model: In four V γ 5 + T cell clones with gene rearrangements in the C γ 1 locus in both alleles, the nonproductive rearrangement involves V γ 2, indicating that V γ 5 + cells are not inherently restricted to rearranging V γ 5 genes 50 . An alternative explanation is that IL-7 activates an unknown cofactor(s) that cooperate with STAT5 in making the locus globally accessible and/or IL-15 activates factors that inhibit accessibility of other V γ genes and/or preferentially target active STAT5 to the V γ 5 gene segment.…”
Section: Discussionmentioning
confidence: 96%
“…An attendant prediction of this model is that all i-IELs with Tcrg gene rearrangements involving the C γ 1 cluster on both chromosomes exclusively exhibit V γ 5 gene rearrangements. However, analysis of Tcrg gene rearrangement pattern in V γ 5 + γδ thymocyte clones does not support this model: In four V γ 5 + T cell clones with gene rearrangements in the C γ 1 locus in both alleles, the nonproductive rearrangement involves V γ 2, indicating that V γ 5 + cells are not inherently restricted to rearranging V γ 5 genes 50 . An alternative explanation is that IL-7 activates an unknown cofactor(s) that cooperate with STAT5 in making the locus globally accessible and/or IL-15 activates factors that inhibit accessibility of other V γ genes and/or preferentially target active STAT5 to the V γ 5 gene segment.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanisms responsible for the absence of cells expressing these Vg/Vd combinations have not been directly analyzed, but in experiments analyzing TCR-g and TCR-d rearrangements in adult gd thymocytes, in isotypically included gd T cells, a correlation was found between the presence of functional Vg2 or Vg4 chains not expressed at the cell surface and that of Vd chains that are not found co-expressed with them. These results were interpreted as an indication that Vg2 and Vg4 chains are very selective in their ability to form stable complexes with TCR-d chains [22]. Indeed, transduction of functional Vg2 and Vd6 chains in a CD3 + cell line resulted in the undetectable expression of a gd TCR at the cell surface giving further support to this notion [24].…”
mentioning
confidence: 77%
“…Indeed, transduction of functional Vg2 and Vd6 chains in a CD3 + cell line resulted in the undetectable expression of a gd TCR at the cell surface giving further support to this notion [24]. Similar phenotype analyses performed in humans have revealed that Vd2 (see [9] for the different nomenclatures of TCR-g and TCR-d genes in humans) is rarely, if ever, used in conjunction with Vg segments other than Vg9 and, conversely, that Vd1 is mostly used together with upstream members of the Vg1-gene family [9] and that these preferences cannot be explained by physical constrains in their associations [25].The present study was undertaken to evaluate the mechanisms responsible for the absence of gd T cells bearing defined Vg/Vd combinations observed in normal adult mice [4,22]. By infecting CD3 + cells with retroviral particles containing the most frequently utilized TCR-g and TCR-d chains we have now formally shown that certain Vg/Vd combinations fail to express on the cell surface indicating that physical constrains in their assembly, rather than liganddriven selection, restrict the V-gene usage of adult mouse gd T cells.…”
mentioning
confidence: 99%
“…The finding that there are no gd committed DN2 cells in WT mice, in contrast to their Tg counterparts, is not unexpected. The stochastic nature of the rearrangement process, together with the fact that not all combinations of TCRg and TCRd are expressed at the cell surface (11,42), results in many daughter cells being unable to express TCRgd. However, a major implication of this finding is that progenitor cells that fail to express a selectable TCRgd still retain the potential to differentiate into ab-lineage cells.…”
Section: Discussionmentioning
confidence: 99%
“…Progression beyond the DN3 stage requires surface expression of either TCRgd or a pre-TCR (7,8), composed of a TCRb-chain paired with an invariant pre-TCRachain (9). Formation of a productive TCRgd allows the development of gd T cells that remain DN (8,10,11). Development of gd-lineage cells is accompanied by increased transcription of TCRd and, presumably, TCRg genes (12).…”
mentioning
confidence: 99%